Enhanced Blood Clotting After Rewarming From Experimental Hypothermia in an Intact Porcine Model - Schanche, Torstein; Filseth, Ole Magnus; Østerud, Bjarne; Kondratiev, Timofei V.; Sieck, Gary C.; Tveita, Torkjel (Frontiers in Physiology, 2022)
IIntroduction: Due to functional alterations of blood platelets and coagulation enzymes at low temperatures, excessive bleeding is a well-recognized complication in victims of accidental hypothermia and may present a great clinical challenge. Still, it remains largely unknown if hemostatic function normalizes upon rewarming. The aim of this study was to investigate effects of hypothermia and rewarming on blood coagulation in an intact porcine model. Methods: The animals were randomized to cooling and rewarming (n=10), or to serve as normothermic, time-matched controls (n=3). Animals in the hypothermic group were immersion cooled in ice water to 25°C, maintained at 25°C for one h, and rewarmed to 38°C (normal temperature in pigs) using warm water. Clotting time was assessed indirectly at different temperatures during cooling and rewarming using a whole blood coagulometer, which measures clotting time at 38°C. Results: Cooling to 25°C led to a significant increase in hemoglobin and hematocrit, which persisted throughout rewarming. Cooling also caused a transiently decreased white blood cell count and increased red blood cell count that returned to baseline levels upon rewarming. After rewarming from hypothermia, clotting time was significantly shortened compared to pre-hypothermic baseline values. In addition, platelet count was significantly increased. Discussion/Conclusion: We found that clotting time was significantly reduced after rewarming from hypothermia. This may indicate that rewarming from severe hypothermia induces a hypercoagulable state, in which thrombus formation is more likely to occur.